Apnea Monitor Using Pulse Oxymetry with Tactile Stimulation to Reduce Respiration Failure - Levana Forra Wakidi; I Dewa Hari Wisana; Anita Miftahul Maghfiroh; Vijay Kumar Sharma (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
Respiratory failure (apnea) often occurs in premature babies, this should be avoided because it causes low oxygen concentrations in the blood so that it can damage brain function and lead to death. Apnea is characterized by a decrease in oxygen saturation (SpO2). The purpose of this study was to design an apnea monitor that was detected with SpO2 parameters, alarms, and vibrating stimulation. This study uses infrared and red LEDs that emit light through the surface of the finger and is detected by a photodiode sensor, this light signal will be converted into an electrical signal and calculated by Arduino to determine the patient's SpO2 and BPM values. If the SpO2 value drops 5% within 5 seconds from the baseline, the device will indicate apnea has occurred and the vibrating motor is working. SpO2 signals and alarms are sent to the nurse station computer via Bluetooth HC-05. The instrument was calibrated with an SpO2 calibrator and the measurement results were compared with a BION pulse oximetry brand. The results of the instrument measurement on two subjects on the SpO2 parameter showed an error value of 2% and the BPM parameter obtained an error value of 4.54%. Testing the BPM parameter using a calibrator at the 30 and 60 BPM settings shows an error value of 0% and at the 120 BPM setting the error value is 0.01%. The vibrating motor to stimulate the baby's body when apnea occurs is functioning properly. The results showed that measurements using subjects tended to have high error values ​​due to several factors. This research can be implemented on patient monitors to improve patient safety and reduce the workload of nurses or doctors